Elimination of China Custom Transit: a Case Study of the Cooperation between Qingdao Port and Zhengzhou Dry Port - Xiao, Xi (2015)
Custom transit is one step of custom clearance which is faced by many exporters when they export goods from the mainland of China. The transit formality requires exporters to preform custom declaration in the local custom and to do a custom transit in the port of departure. Such procedures aim to keep the export goods under custom control. Although custom transit indeed safeguards the goods on the way, it actually complicates the custom clearance formalities and increases the transaction cost of the international trade. Therefore, simplifying custom transit procedures could bring benefits to China export business, which contributes to approximately 12% of world export values in recent years (World Trade Organisation, 2015).